Influence of boron treatments on fatty acid desaturase metabolism in different safflower cultivars - Ekrem Bolukbasi (Plant, Soil and Environment, 2022)
This study investigated the expression levels of FAD2 genes important for the conversion of oleic acid to linoleic acid at cotyledon, root and leaf tissues of four different safflower cultivars (Olas, Remzibey, Dincer and Gokturk) subjected to B by qRT-PCR. Safflower species were grown in a controlled environmental growth chamber for 21 days and then exposed to different B concentrations ranging from 20 to 1 280 μmol for 24 h. RNA isolation, cDNA synthesis and RT-PCR analysis were performed on root, cotyledon and leaf tissues exposed to B stress for 24 h. It was determined that the expression levels of FAD2 genes decreased in the safflower cultivars exposed to increasing B concentrations. Under B stress conditions, the expression levels of FAD2 genes revealed an overall pattern of increase and reduction up to 160 μmol relative to the control group, and they reached the highest expression level. After 320 μmol, the activity of FAD2 genes was almost absent at increasing concentrations. All results show that the application of B causes significant changes in the expression of FAD2 genes and plays an important role in the defence mechanism against increased B toxicity.